Student perception towards medical waste disposal management in Pusat Kesihatan Universiti Utara Malaysia (PKU) - Azizh, Siti Aisyah; Mad Lazim, Halim (Universiti Utara Malaysia, 2020)
The objective of this study was to assess the knowledge, awareness and perception of UUM students regarding medical waste disposal management in PKU. A self-ministered questionnaire consisting of 24 questions on knowledge, awareness, and students’ satisfaction about medical waste management was distributed among 100 students randomly from three different colleges which were COB, CAS and COLGIS. The data extracted were tabulated, and statistically analyzed using SPSS version 25 where results were obtained. The majority of UUM students have moderate level of knowledge regarding medical waste disposal management in PKU. Nevertheless, majority UUM students have a good level of awareness about medical waste disposal and also have good satisfaction level regarding the services provided in PKU. Female students have higher level of knowledge and awareness about medical waste disposal when compared with male students. Hence, these findings imply that medical talk programs are required for students who have no medical knowledge. This is to motivate the students to learn and gain awareness regarding the medical waste management.